Artificial Intelligence in Recruitment: Navigating the Era of Web 4.0 - Hamza Melliani; Imane Mouhtat; Wafa Kerfal; Ayoub Razouk (Qubahan Academic Journal)
As digitalization puts everything into question, companies are becoming increasingly aware of the digital transformation that is challenging the way they react to their global ecosystem (Léon & Dejoux, 2018). AI has taken its place in our current lives; it has penetrated human life on all levels (the professional level is no exception) including recruitment which in turn finds itself faced with this technology (Mallard, 2018). This study aims to analyze the perceived adoption of artificial intelligence in recruitment through a systematic literature review and descriptive statistical analysis. Focusing on the private sector in Morocco, the study examines AI adoption challenges in five sectors: administration and office automation, human resources, production and manufacturing, finance and accounting, and education. The study was carried out by means of a questionnaire sent by e-mail to a pre-defined sample of companies. We received 66 responses. After removing the outliers, the final sample size was 60. Based on flat analyses, the results show a perception of job losses in the human resources and education sectors. Despite the advantages of AI, notably in terms of rapid processing and sorting of applications, as well as task automation. Private sector companies in Morocco operating in the five sectors defined in this study face AI adoption challenges due to a lack of resources.